The Enterococcus Cassette Chromosome, a Genomic Variation Enabler in Enterococci - A. Sivertsen (American Society for Microbiology, 2018)
ABSTRACT Enterococcus faecium has a highly variable genome prone to recombination and horizontal gene transfer. Here, we have identified a novel genetic island with an insertion locus and mobilization genes similar to those of staphylococcus cassette chromosome elements SCCmec. This novel element termed the enterococcus cassette chromosome (ECC) element was located in the 3′ region of rlmH and encoded large serine recombinases ccrAB similar to SCCmec. Horizontal transfer of an ECC element termed ECC::cat containing a knock-in cat chloramphenicol resistance determinant occurred in the presence of a conjugative reppLG1 plasmid. We determined the ECC::cat insertion site in the 3′ region of rlmH in the E. faecium recipient by long-read sequencing. ECC::cat also mobilized by homologous recombination through sequence identity between flanking insertion sequence (IS) elements in ECC::cat and the conjugative plasmid. The ccrABEnt genes were found in 69 of 516 E. faecium genomes in GenBank. Full-length ECC elements were retrieved from 32 of these genomes. ECCs were flanked by attR and attL sites of approximately 50 bp. The attECC sequences were found by PCR and sequencing of circularized ECCs in three strains. The genes in ECCs contained an amalgam of common and rare E. faecium genes. Taken together, our data imply that ECC elements act as hot spots for genetic exchange and contribute to the large variation of accessory genes found in E. faecium. IMPORTANCE Enterococcus faecium is a bacterium found in a great variety of environments, ranging from the clinic as a nosocomial pathogen to natural habitats such as mammalian intestines, water, and soil. They are known to exchange genetic material through horizontal gene transfer and recombination, leading to great variability of accessory genes and aiding environmental adaptation. Identifying mobile genetic elements causing sequence variation is important to understand how genetic content variation occurs. Here, a novel genetic island, the enterococcus cassette chromosome, is shown to contain a wealth of genes, which may aid E. faecium in adapting to new environments. The transmission mechanism involves the only two conserved genes within ECC, ccrABEnt, large serine recombinases that insert ECC into the host genome similarly to SCC elements found in staphylococci.